Dialister massiliensis sp. nov., a new bacterium isolated from the human gut. (March 2020) - Afouda, P.; Dubourg, G.; Tomeï, E.; Raoult, D.; Fournier, P.-E.
Abstract: Dialister massiliensis strain Marseille-P5638 T (= CSUR P5638) is a new species from the genus Dialister and family Veillonellaceae which was isolated from the gut microbiota of a healthy individual.